EP 6. Longitudinal resting state functional connectivity patterns in the early phase of recovery from Aphasia in temporoparietal stroke. Issue 9 (September 2016) - Klingbeil, J.; Stockert, A.; Wawrzyniak, M.; Wrede, K.; Saur, D.
Abstract : Background: Poststroke aphasia recovery evolves in space and time. Substantial language improvements can be observed within the first days after stroke. However, underlying changes in the functional status of the language network during the acute phase remain to be demonstrated. Methods: In a resting-state functional connectivity (RSFC) fMRI study we assessed changes in functional connectivity repeatedly (acute( t 1) = 2 ± 1, subacute( t 2) = 10 ± 2 days post-onset) in aphasic patients ( N = 12, 62 ± 14 years, 10 male) with left temporoparietal stroke. Language comprehension and production scores were calculated based on the Aachener Aphasie-Test. For RSFC analysis 9mm spherical ROIs reflecting core language regions in the left anterior inferior frontal (aIFG: x = −54 y = 32 z = 1, MNI-space), posterior middle temporal gyrus (pMTG: x = −54 y = −43 z = 4) and their right hemisphere homologous were selected. Results: Seed-to-whole-brain analysis from left aIFG or pMTG revealed RSFC to right hemisphere homologous frontal or temporal areas at t 1 and t 2 ( p > .05, FWE corrected). Longitudinally, RSFC from left pMTG to left aIFG as well as RSFC from left aIFG to left frontal (operculum, insula, premotor cortex) and to right frontal (IFG, premotor cortex) areas increased significantly from t 1 to t 2 ( p > .001, uncorrected). Subsequent ROI-to-ROI analysis revealed increased RSFC between left aIFG and pMTG from t 1 to t 2 associated with improved language production ( r = .579, p = .049). During the acute phase ( t 1) better scores for language comprehension and production were predicted by higher RSFC between left aIFG and right aIFG ( r = .736 p = .006). Conclusion: We observed early ipsi- and contralesional changes in the language network's functional connectivity and associated language improvements indicative of acute diaschisis and subsequent reorganization within the distributed language network.